Antibiotic resistance, virulence and biofilm forming capacity of acinetobacter baumannii isolated from Goranchatbari sub-catchment in Dhaka city - Haque, Nayeema (Brac University, 2024)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2023.